Association of Genetic Variants With Moyamoya Disease in 13 000 Individuals: A Meta-Analysis. Issue 6 (June 2020) - Wang, Xiaotong; Wang, Yue; Nie, Fangfang; Li, Qian; Zhang, Kaili; Liu, Mengwei; Yang, Luping; Zhang, Qian; Liu, Shan; Zeng, Fanxin; Shang, Mengke; Liang, Man; et al.
Abstract : Background and Purpose—: A growing body of evidence indicates genetic components play critical roles in moyamoya disease (MMD). Firm conclusions from studies of this disease have been stymied by small sample sizes and a lack of replicative results. This meta-analysis was conducted to determine whether these genetic polymorphisms are associated with MMD. Methods—: PubMed, Google Scholar, Embase, Wanfang, Web of Science, and China National Knowledge Infrastructure databases were used to identify potentially relevant studies published until January 2020. The Review Manager 5.2 and Stata 15.0 software programs were used to perform the statistical analysis. Heterogeneity was assessed using the Cochran Q test and quantified using the I 2 test. Results—: Four thousand seven hundred eleven MMD cases and 8704 controls in 24 studies were included, evaluating 7 polymorphisms in 6 genes. The fixed-effect odds ratios (95% CI) in allelic model of MMP-2 rs243865 were 0.60 (0.41–0.88) ( P =0.008). In the country-based subgroup analysis, the fixed-effect odds ratios (95% CI) of RNF213 rs112735431 in allelic model were China, 39.74 (26.63–59.31), Japan, 74.65 (42.79–130.24) and Korea, 50.04 (28.83–86.88; all P <0.00001). In the sensitivity analysis, the fixed-effect odds ratios (95% CI) of allelic and dominant models were the RNF213 rs148731719 variant, 2.17 (1.36–3.48; P =0.001), 2.20 (1.35–3.61; P =0.002), the TIMP-2 rs8179090 variant, 0.33 (0.25–0.43; P <0.00001), 0.88 (0.65–1.21; P =0.440) and the MMP-3 rs3025058 variant, 0.61 (0.47–0.79; P =0.0002), 0.55 (0.41–0.75; P =0.0001), respectively. Conclusions—: RNF213 rs112735431 and rs148731719 were positively, and TIMP-2 rs8179090, MMP-2 rs243865, and MMP-3 rs3025058 were inversely associated with MMD using multiple pathophysiologic pathways. Studies in larger population should be conducted to clarify whether and how these variants are associated with MMD. Abstract : Supplemental Digital Content is available in the text.